Ojo Kawin Bocah Peran Komunikasi Keluarga dalam Pencegahan Pernikahan Anak di Kecamatan Keling Kabupaten Jepara - Siti Asiyah; Mulin Ni'am (Kifah: Jurnal Pengabdian Masyarakat, 2022)
The large number of child marriage cases in Indonesia has resulted in various new problems such as the disconnection of school children, the increase in divorce cases, the increasing mortality rate for mothers and children during the delivery process, the number of stunting cases and other problems. Looking at the various problems that exist, there is a change in the marriage law from Law No. 1 of 1974 to Law No. 16 of 2019 that marriage can be carried out by both men and women when they are 19 years old. Through the Asset Bassed Community Development (ABCD) method, Community Service (PkM) activities are carried out by providing counseling to the community (parents and children) in Klepu Village and Watuaji Village, Keling District to provide an understanding of the Importance of Family Communication in preventing child marriage. With this PkM, it is hoped that it will be able to provide understanding to the community so that awareness arises about the dangers and impacts of child marriage and can reduce cases of child marriage.